ELECTRIC POTENTIAL MEASUREMENT AND MODELING IN THE VICINITY OF THE METAL ELECTRODES IN SAND MEDIA - Martha Kenek Udak, Anastasia
In the Final Project (PA) 1, Study of Changes in Electric Potential Difference in Sand Using Metal Electrodes which aims to investigate the effect of using metal electrodes on the measurable potential difference of dry sand has been conducted. Measurement was performed by means of the Rigol DM3058E digital multimeter without non-polar electrodes. The results show that the measured electric potential difference of the sand is a function of time, which is assumed to occur due to the polarization of the electric charge on the surface of the metal electrodes or inside the sand. However, the source of the external electric field causing the polarization has not been determined yet. In the Final Project 2 (PA 2), due to the Covid-19 pandemic, the PA 1 research could not be continued and was shifted to model electric potential due to metal rod as potential electrodes. The type of charged rod that used is a non-conducting charged rod with line charge type that has total charge of Q and length of rod L. The numerical method used in the simulations with VBA Excel is the numerical integration method with the trapezoidal rule. These data are used to analyze the effect of variations in the position and length of the charged rod. The results show that when the charged rod is getting longer then the height of the peak of the electric potential, the height of the peak of the electric potential difference, and the center width of the electric potential contour are getting smaller, respectively. Meanwhile for the contour of the electric potential difference, when the charged rod is getting longer then the center width of the contour is getting bigger.